PERBANDINGAN AKURASI PENDUGAAN BOBOT BADAN SAPI BALI (Bos sondaicus) MENGGUNAKAN RUMUS LAMBOURNE, SCHROOL DAN DJAGRA (Accuracy comparison of body weight estimation of bali cattle (Bos sondaicus) using lambourne, schrool and djagra formulas) - Muhammad Kurniawan Dwi Septyan; Servis Simanjuntak; Ari Wibowo; Suhardi Suhardi (Universitas Nusa Cendana, 2023)
The predominant method of cattle sale in Indonesia relies on estimation through visual assessment of body characteristics (jogrog). Achieving precise body weight estimates is crucial to enhance accuracy and prevent discrepancies in transactions involving the purchase and sale of beef cattle. This study aimed to establish a formulaic approach for calculating body weight that closely approximates measured values and identify constants in the predictive formula that align with actual measurements. The evaluation included assessing variations in body weight prediction methods using the Lambourne, Schrool, and Djagra formulas, based on heart girth and body length. Formula tests were conducted to identify the estimation formula that best approximated actual body weight. The research, carried out from April to May 2023 at CV. Sentra Sapi Kalimantan, involved 43 male Bali cattle (Bos sondaicus) aged 1.5-2.5 years. Results at CV. Sentra Sapi Kalimantan indicated an average heart girth of 136.89±7.05 cm, body length of 111.22±5.10 cm, and body weight of 192.62±26.62 kg. Data analysis was performed by calculating deviation percentage and linear regression analysis, revealed a substantial deviation of 37.37±13.83% between the Schrool formula and actual weight. In contrast, the Lambourne and Djagra formulas exhibited non-significant deviations of 8.73±6.86% and 8.54±6.29%, respectively. Conclution base on accuracy comparison of body Weight estimation of Bali cattle (Bos sondaicus) using Lambourne, Schrool and Djagra formulas found constanta and effective formula to estimate real cobt weight of Bali cattle: BW = -276.423 + 3.468 HG (cm) – 0.077 BL (cm).